Extensive Families of miRNAs and PHAS Loci in Norway Spruce Demonstrate the Origins of Complex phasiRNA Networks in Seed Plants - Xia, Rui (Oxford University Press, 2015)
In eudicot plants, the miR482/miR2118 superfamily regulates and instigates the production of phased secondary small interfering RNAs (siRNAs) from NB-LRR (nucleotide binding leucine-rich repeat) genes that encode disease resistance proteins. In grasses, this miRNA family triggers siRNA production specifically in reproductive tissues from long noncoding RNAs. To understand this functional divergence, we examined the small RNA population in the ancient gymnosperm Norway spruce (Picea abies). As many as 41 miRNA families in spruce were found to trigger phasiRNA (phased, secondary siRNAs) production from diverse PHAS loci, with a remarkable 19 miRNA families capable of targeting over 750 NB-LRR genes to generate phasiRNAs. miR482/miR2118, encoded in spruce by at least 24 precursor loci, targets not only NB-LRR genes to trigger phasiRNA production (as in eudicots) but also noncoding PHAS loci, generating phasiRNAs preferentially in male or female cones, reminiscent of its role in the grasses. These data suggest a dual function of miR482/miR2118 present in gymnosperms that was selectively yet divergently retained in flowering plants. A few MIR482/MIR2118 precursors possess an extremely long stem-loop structure, one arm of which shows significant sequence similarity to spruce NB-LRR genes, suggestive of an evolutionary origin from NB-LRR genes through gene duplication. We also characterized an expanded miR390-TAS3 (TRANS-ACTING SIRNA GENE 3)-ARF (AUXIN RESPONSIVE FACTOR) pathway, comprising 18 TAS3 genes of diverse features. Finally, we annotated spruce miRNAs and their targets. Taken together, these data expand our understanding of phasiRNA network in plants and the evolution of plant miRNAs, particularly miR482/miR2118 and its functional diversification.